The development of halal food industry in Bangka Belitung Island: an analytic network process - Suhel Suhel; Mukhlis Mukhlis; Abdul Bashir; Eka Fitriyanti (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This study analyzes the development of the halal food industry in Bangka Belitung Island. Development is measured by innovation strategy, product strategy, promotion strategy, pricing strategy, and collusion strategy. The data used are primary data obtained from in-depth interviews with five experts and practitioners with competent considerations in the field of the halal food industry—the analysis technique applying the Analytic Network Process. The findings indicated that the most superior aspects in the behavioral cluster are innovation strategy, product strategy, promotion strategy, price strategy, and collusion strategy. Meanwhile, the result from the benefit, cost, opportunity, risk (BOCR) cluster, the order of aspects that best describes the condition of the halal food industry in Bangka Belitung, is an opportunity, benefit, cost, risk. It is hoped that there will be a joint commitment from policy-makers in supporting and encouraging efforts to develop the halal food industry in Indonesia. It is expected that industry agents can further optimize industrial behavior, especially promotion and collaboration strategies.